MBCL-50. SAFETY AND EFFICACY OF CHEMOTHERAPY INTENSIFICATION WITH AUTOLOGOUS HEMATOPOIETIC STEM CELL RESCUE, WITHOUT RADIATION, FOR CHILDREN WITH CNS EMBRYONAL TUMORS. Issue 2 (22nd June 2018) - Bavle, Abhishek; Gross, Naina; Gavula, Theresa; Confer, Michael; Peterson, Jo Elle; Fung, Kar-Ming; Rooms, Laura; Crawford, David; McNall-Knapp, Rene
Abstract: INTRODUCTION: Survival for children with central nervous system (CNS) embryonal tumors has improved significantly with craniospinal irradiation, but at the cost of long-term adverse effects including second malignancies and significant neurocognitive deficits. One strategy to achieve cure, while avoiding radiation, is intensification of chemotherapy. We report our experience with this approach in 9 patients with embryonal tumors, whose parents declined radiation therapy. METHODS: Four patients with medulloblastoma (MB) (median age 2.6 years; 2 classic/M0, 1 anaplastic/M1, 1 desmoplastic-nodular/M0/SHH; 3 non-WNT, non-SHH; none MYCN amplified) and 5 patients with localized non-MB embryonal tumors (median age 3.7 years; 4 ETMR, 1 NOS) were treated per ACNS0334 (3 cycles of vincristine, cyclophosphamide, cisplatin, etoposide, then consolidation with 3 cycles of carboplatin, thiotepa with autologous hematopoietic stem cell rescue). RESULTS: Three of 4 patients with MB are alive a median of 3 years (1.5 - 4.5y) off-therapy; one patient is deceased secondary to congenital heart disease (germline NAA10 mutation) 1.4 years off-therapy. Of 5 non-MB patients, 3 are alive - 1 without radiation 3.4 years off-therapy; 2 after focal radiation for local progression. Median time to progression for 4 patients was 5 months. Grade 3 adverse events for all patients included mucositis, pancytopenia and fever/neutropenia (median 5 episodes), with no therapy-related deaths. CONCLUSIONS: Intensified chemotherapy is a promising strategy to treat select MB patients without radiation, but appears less effective for non-MB embryonal tumors. Evaluation of the efficacy and safety of this approach for MB, with prospective trials informed by tumor biology, is warranted.